ANALYSIS OF SOCIALIZATION OF NON-CASH PAYMENTS THROUGH QRIS TO THE MERCHANTS OF NUSUKAN SURAKARTA TRADISIONAL MARKET - MADDA ASYAFA PUTRA; MIFTAHUL NUR UTAMI AMALIA SHOLIHA; DWI ARIES HIMAWANTO (CV KULTURA DIGITAL MEDIA, 2022)
This community service activity aims to increase the understanding of the Nusukan Surakarta Traditional Market merchants towards non-cash payment methods by utilizing the QRIS (Quick Response Indonesia Standard) barcode. This education is carried out by cooperating with partner from Permata Bank Surakarta in the form of a webinar through the Google Meet platform aimed at market merchants, as well as door to door outreach to their stalls. Through this outreach activity, merchants have a better understanding of the use of QRIS and the importance of implementing this cashless payment system in the future. The QRIS socialization conducted at the Nusukan Market has an impact on new knowledge for merchants about cashless payments and opening access for merchants who want to use QRIS. However, the limited access to technology by them is one of the constraining factors in this socialization.